Music-based neurofeedback system for stress regulation and memory stimulation (2020)
Although musical neurofeedback is used in multiple works, few systems have been developed for stress regulation, and no systems have been developed for memory stimulation. For this reason, a music-based neurofeedback system for stress regulation and memory stimulation is proposed. This system was designed as a response to a previous research called “Neurophysiology of Emotions and Intimate Partner Violence (IPV) against Women”. The designed system uses 8 EEG channels to analyze alpha and theta brain-waves from 4 areas of the brain: prefrontal, frontal, temporal and central. By recording a 30 seconds baseline, the system is capable to detect changes in the EEG signal that can be used for the interaction. For feedback, three musical features are modified depending on the EEG analysis: tempo, loudness and loudness of the voice of the singer. For testing the system, two protocols were designed, these protocols focused on memory stimulation and stress regulation. They were designed specifically for each one of the three types of feedback. These protocols were applied on two women (43 and 52 years old), both had been part of the previous project. Results are promising, showing changes in the EEG signals of the participants when comparing the first session and the last one. Changes in performance of some specific tasks in the protocols, show an adequate usability of the system. Further studies will be carry on in order to evaluate long-term effects of the system with more activities.